Contaminação por nitrato no Aquífero Adamantina: o caso do município de Monte Azul Paulista - SP - Montanheiro, Filipe [UNESP] (2014)
The municipality of Monte Azul Paulista is stocked exclusively by groundwater through aquifers drilled in Adamantina and Serra Geral deep wells. In recent years, there were high concentrations of nitrate in groundwater, a fact that prevented the use of some wells for public supply. From the interpretation and integration of hydrochemical, hydrogeological and geophysical results, it was possible to develop a conceptual model for the municipality, in order to provide technical support for better management of the groundwater resource. With the chemical analysis of water was possible to identify two hydrochemical types in the city: the calcium bicarbonate waters, which are those associated with no or low influence of anthropogenic contamination, and chlorinated calcic waters, which correlate with the waters under the influence of nitrate contamination. The hydrogeology of the city was characterized by presenting two distinct water level. The top, located between the surface and 40 meters deep and the bottom between 80 and 150 meters deep. Isolating these two aquifers was identified a layer of clayey sediments, 40 meters thick. In 152 meters depth, occur the basalts of the Serra Geral Formation. High concentrations of nitrate in groundwater are related to infiltration of domestic effluents from septic tanks and leaking sewer pipes. Although it is known that this contaminant is from the surface, it was noticeable that he ever distributed by the deep aquifer, and is not restricted only to the superficial layers. The hydrochemistry had an important role in understanding and confirmation that there is a mix between surface contaminated aquifer and the deep aquifer, which is increasingly becoming contaminated. For this simulation was taken from a mixture of contaminated surface water with deep water with no or very low nitrate concentration. From this simulation, it could be noted that the different mixture proportions generated by mathematical...